Introduced mangroves escape damage from marine and terrestrial enemies. Issue 3 (30th January 2022) - Davidson, Timothy M.; Smith, Celia M.; Torchin, Mark E.
Abstract: The enemy release hypothesis (ERH) posits that introduced species often leave their enemies behind when introduced to a new range. This release from enemies may allow introduced species to achieve higher growth and reproduction and may explain why some invaders flourish in new locations. Red mangroves ( Rhizophora mangle ) were introduced to Hawaiʻi from Florida over a century ago. Because Hawaiʻi has no native mangroves, the arrival of R. mangle fundamentally changed the structure and function of estuarine shorelines. While numerous enemies affect red mangroves in their native range (tropical America), in Hawaiʻi, mangroves apparently experience little herbivory, which may explain why introduced mangroves are so productive, fecund, and continue to spread. In this study, we compared the effects of enemies in native and introduced populations of brackish red mangroves ( R. mangle ) in 8–10 sites in the native range (Florida, Belize, and Panama) and introduced range of mangroves (Hawaiʻi). At each site, we measured the (1) occurrence of enemies using timed visual surveys, (2) occurrence of damage to different mangrove structures (leaves, apical buds, dead twigs, roots, propagules, and seedlings), and (3) rate of propagule herbivory using tethering experiments. Consistent with the ERH, we found an order of magnitude less damage and fewer enemies in introduced than native mangrove sites. While introduced mangroves harbored few enemies and minimal damage, native mangroves were affected by numerous enemies, including leaf‐eating crabs, specialist bud moths, wood‐boring insects and isopods, and propagule predators. These patterns were consistent across all plant structures (roots to leaves), among marine and terrestrial enemies, and across functional groups (browsers, borers, pathogens, etc.), which demonstrates enemy escape occurs consistently among different functional groups and via trophic (e.g., herbivores) and non‐trophic (e.g., root borers) interactions. Our study is among the first biogeographical enemy release studies to take a comprehensive approach to quantifying the occurrence of damage from a broad suite of marine and terrestrial taxa across an array of wetland plant structures. Understanding how natural enemies alter this key foundation species will become increasingly relevant globally as mangroves continue to invade new regions through intentional plantings or range expansion driven by climate change.